(untitled) (Bangladesh Journal of Animal Science, 2012)
A study was conducted in two southern coastal districts of Bangladesh (Noakhali and Lakshmipur) to assess the potentiality of the existing duck rearing system of the regions in summer and rainy season. One upazila from each district and three villages from each upazila were selected randomly. Fifty farmers were selected from each village having at least 5 ducks throughout the year. Thus, a total of 300 farmers were selected for this study. The informations were collected by using an interview schedule. The majority of the farmers (39%) belonged to middle-aged category. Thirty per cent farmers have got primary level of education. About 50 per cent farmers had large family size having an average of 7 persons per family. Twenty seven per cent farmers had small land size with an average of 1.00 ha per household. Sixty one per cent of the respondents considered agriculture as a main occupation. About 99 per cent farmers annually earned Taka 1502.00 from duck rearing. The majority of farmers (82.25%) are rearing Desi ducks followed by Crossbred (12%) and Hybrid (5.75%). Forty four per cent of the farmers cleaned their duck houses 2-3 times in a month whereas only 11 per cent cleaned their duck houses everyday, 22 per cent once in month, 18 per cent 4-6 times in a month and 5 per cent farmers cleaned their duck houses 7-10 times in a month. About 39 per cent farmers reared ducks under scavenging system with only natural feed resources and 61.5 per cent farmers used supplemental feed, mainly rice polish (118 g/bird/day) in summer season. Eighty five per cent farmers in both districts did not use vaccines against duck diseases. However, 10 per cent of the farmers buried their dead ducks somewhere else. It was found from the study that 70 per cent farmers preferred to sell their eggs and ducks to the foria and in local market. It was also observed that duck raising would be more profitable business if the problems related to it could be solved. In terms of profitability, income and employment generation, duck rearing appeared to be a promising sub-sector in agriculture. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9922 BJAS 2009; 38(1-2): 132-141